The crane flies (Diptera: Tipuloidea) of Great Smoky Mountains National Park - Petersen, Matthew J.; Parker, Charles R.; Bernard, Ernest (Zootaxa, 2005)
The list of crane flies (Diptera: Ptychopteridae, Tipuloidea, Trichoceridae) known from Great Smoky Mountains National Park is updated. Sampling in association with the All Taxa Biodiversity Inventory of Great Smoky Mountains National Park resulted in the addition of 107 new Park records, bringing the current list to 250 species. This species assemblage is much richer than those of surrounding areas, although similar in composition. Total richness is estimated to be between 450 and 500 species for Great Smoky Mountains National Park.